2013
DOI: 10.1111/mec.12420
|View full text |Cite
|
Sign up to set email alerts
|

Late‐glacial recolonization and phylogeography of European red deer (Cervus elaphus L.)

Abstract: The Pleistocene was an epoch of extreme climatic and environmental changes. How individual species responded to the repeated cycles of warm and cold stages is a major topic of debate. For the European fauna and flora, an expansion-contraction model has been suggested, whereby temperate species were restricted to southern refugia during glacial times and expanded northwards during interglacials, including the present interglacial (Holocene). Here, we test this model on the red deer (Cervus elaphus) a large and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
127
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 70 publications
12
127
0
2
Order By: Relevance
“…It has specifically been stated that only ancient DNA (aDNA) analyses of indigenous Italian mainland red deer could settle the question of the origin of the Tyrrhenian red deer 8 . Ancient DNA studies have revealed that the present distribution of phylogeographic lineages may be more limited than before the anthropogenic impacts on large mammal populations, including those of red deer 27 (for an example in brown bears see refs 28,29 ). They have also been performed to elucidate the recolonization of Scandinavia 30 and specifically to address the colonization of islands: Carden et al .…”
Section: Introductionmentioning
confidence: 99%
“…It has specifically been stated that only ancient DNA (aDNA) analyses of indigenous Italian mainland red deer could settle the question of the origin of the Tyrrhenian red deer 8 . Ancient DNA studies have revealed that the present distribution of phylogeographic lineages may be more limited than before the anthropogenic impacts on large mammal populations, including those of red deer 27 (for an example in brown bears see refs 28,29 ). They have also been performed to elucidate the recolonization of Scandinavia 30 and specifically to address the colonization of islands: Carden et al .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers sampled modern and ancient red deer specimens from the entire European range of the species over the last c. 40,000 years [14]. Results described two main European red deer groups: West/central Europe vs South-East Europe and Western Asia arose by red deer expansions from Iberia and Balkans refugia (and possibly from Italy as well) in the last post-glacial warming.…”
Section: Introductionmentioning
confidence: 99%
“…The timing and nature of the Solutrean-Magdalenian transition (pre-or post-17,000 uncal BP; abrupt or gradual) have been the subjects of debate in SW Europe for many decades, especially with the recent claims for a widespread Badegoulian technocomplex or tradition interposed between the Solutrean and the classic Magdalenian in Spain as well as in France, where it had originally been defined. The El Mirón burial is the first Magdalenian interment to be discovered on the Iberian Peninsula, although (in line with Magdalenian traditions in France and Germany, as summarized by Pettitt [2011]) there is other evidence in Spain of the postmortem manipulation of human remains, including the cranial "cups" found by Obermaier (1924) (Meiri et al 2013). Information on the Oxford laboratory's ultrafiltration pretreatment, target preparation, and AMS measurement methods is published in Bronk Ramsey et al (2002) and Higham et al (2006).…”
Section: Introductionmentioning
confidence: 95%